Global age-sex-specific fertility, mortality, healthy life expectancy (HALE), and population estimates in 204 countries and territories, 1950–2019: A comprehensive demographic analysis for the Global Burden of Disease Study 2019 - GBD 2019 Demographics Collaborators (Elsevier, 2022)
This article was published in The Lancet [ © 2020 The Author(s). Published by Elsevier Ltd. This is an Open Access Article under the CC BY 4.0 license..] and the definite version is available at: https://doi.org/10.1016/S0140-6736(20)30977-6. The Journal's website is at: https://reader.elsevier.com/reader/sd/pii/S0140673620309776?token=460FED42B988FE1EB8DBC15E8F9E524D2A1137C21AE2442A854F6DF4B9C36DABAEB9BE243A2786B8C7B9BDA2FF7CAC45&originRegion=eu-west-1&originCreation=20220522063449